BONDRES DANGDANG KETEKUNG SEBAGAI MEDIA KOMUNIKASI PENDIDIKAN - Niluh Wiwik Eka Putri (UHN IGB Sugriwa Denpasar, 2021)
One of the Balih-balihan arts is bondres. Bondres is often performedin ritual activities in Bali. Bondres is used as a communication medium thatcan educate the public with unique packaging such as displaying funnycharacters, as well as fresh humor. The implementation of ceremonialtraditions and arts for Balinese Hindus is inherent. Bondres DangdangKetekung still exists in the midst of the development of communicationtechnology, it can be proven by the fact that they often fill events in variousactivities in Buleleng Regency. With still active Dangdang Ketekung, itindicates if the community is entertained by his jokes. In addition,Dangdang Ketekung also uses social media such as Facebook, Instagramand YouTube to be better known by the wider community, especially theyounger generation. The communication of education implemented in theDangdang Ketekung bondres mask performance is expected to be able tomake an important contribution in understanding and practicing theinteractions and actions of all individuals involved. In their performances,they understand communication models such as dialogic, persuasive andeducative. So that the teachings of education can be conveyed to thepublic. One of them is about the teachings of Tri Kaya Parisudha, Tri KitaKarana, and topics that are currently trand.